The Role of Emoji in Politeness Strategies in the Comments of Influencer TikTok - Radita Astried Rizkya; Trivera Hana; Reyhan Habib; Rahmadsyah Rangkuti (Lembaga Pengembangan Kinerja Dosen, 2025)
Social media has transformed communication patterns, with TikTok emerging as a platform where interactions are highly expressive and multimodal. This study examines the role of emojis as politeness strategies in the comments section of TikTok influencers, focusing on how these visual symbols help maintain harmonious digital communication. Using a qualitative descriptive approach, the researchers analyzed 20 emoji-containing comments from a high-engagement influencer video. The data were interpreted through Brown and Levinson’s (1987) politeness theory, supplemented by the concept of multimodality. The findings indicate that emojis significantly support both positive and negative politeness strategies. Positive politeness was dominant (around 70%), often realized through empathy, humor, and solidarity-building emojis, while negative politeness was achieved through hedging, apologies, and respectful cues. Emojis also frequently softened bald-on-record statements and enabled off-record indirectness. The study concludes that emojis are crucial in enhancing politeness, enriching emotional expression, and fostering a sense of community in TikTok interactions, highlighting their importance in the evolving landscape of digital sociolinguistics.